Strontium enhances proliferation and osteogenic behavior of bone marrow stromal cells of mesenchymal and ectomesenchymal origins in vitro - Carolina Bizelli‐Silveira; Lisbeth Ann Abildtrup; Rubens Spin‐Neto; Morten Foss; Kjeld Søballe; David Christian Evar Kraft (Wiley, 2019)
Abstract Obejective To investigate the effect of increasing Strontium (Sr) concentrations on the growth and osteogenic behavior of human bone marrow stromal cells (BMSCs) from mesenchymal (i.e., fibula) and ectomesenchymal (i.e., mandible) embryonic origins. Materials and methods Fibula and mandible BMSCs were cultured in media without (Ctrl) or with Sr in four diverse concentrations: Sr1, 11.3 × 10−3 mg/L, human seric physiological level; Sr2, 13 mg/L, human seric level after strontium ranelate treatment; Sr3, 130 mg/L, and Sr4, 360 mg/L. Proliferation rate (1, 3, and 7 days), osteogenic behavior (alkaline phosphatase [ALP] activity, 7 and 14 days; expression of osteogenic genes (ALP, osteopontin, and osteocalcin at 7, 14, and 21 days), and formation of mineralized nodules (14 and 21 days) of the BMSCs were assessed. Data was compared group‐ and period‐wise using analysis of variance tests. Results Fibula and mandible BMSCs cultured with Sr4 showed increased proliferation rate, and osteocalcin and osteopontin gene expression together with more evident formation of mineralized nodules, compared all other Sr concentrations. For both cell populations, Sr4 led to lower ALP activity, and ALP gene expression, compared with the other Sr concentrations. Conclusion BMSCs from mesenchymal (i.e., fibula) and ectomesenchymal (i.e., mandible) embryonic origins showed increased cellular proliferation and osteogenic behavior when cultured with Sr4, in vitro.